Social Capital of Parak and Rimbo Management in West Sumatra - Ferdinal Asmin; Dudung Darusman; Iin Ichwandi; Didik Suharjito (Institut Pertanian Bogor (IPB University), 2017)
The topic of social capital has been gaining many concerns from social researchers throughout the world, especially in collective action perspective. This study aimed to describe the organizational activities of the local forest management practices (parak and rimbo) as a social capital in collective action perspective. The research method is a case study of Koto Malintang and Simancuang people in West Sumatra. Collecting data was conducted by unstructured interviews, field observations, and document studies. Data analysis uses categorization and coding, document analysis, and historical analysis. Our findings were described in the context of decision-making, resources management and mobilization, communication, and conflict resolution. Collective action for decision-making involved the acquisition, allocation, and distribution mechanisms to divide land and forest product among local people. In the context of resources management and mobilization, they applied kinship relations among families, sub-clans, and clans to manage their resources. They then communicated their needs in any formal and informal meetings. When a conflict occurred in related to forest utilization, they applied an adat court to make a win-win solution. Nevertheless, the challenges of collective action are still about the resources availability, benefit equity, and external supports